Co-delivery of doxorubicin and SATB1 shRNA by thermosensitive magnetic cationic liposomes for gastric cancer therapy. - Zhao Peng; Chenxiao Wang; Erhu Fang; Xiaoming Lu; Guobin Wang; Qiang Tong (PLoS ONE, 2014)
In previous a study, we had developed a novel thermosensitive magnetic delivery system based on liposomes. This study aimed to evaluate the efficiency of this system for the co-delivery of both drugs and genes to the same cell and its anti-tumor effects on gastric cancer. Doxorubicin (DOX) and SATB1 shRNA vector were loaded into the co-delivery system, and in vitro DOX thermosensitive release activity, targeted gene silencing efficiency, targeted cellular uptake, in vitro cytotoxicity, as well as in vivo anti-tumor activity were determined. The results showed that this co-delivery system had desirable targeted delivery efficacy, DOX thermosensitive release and SATB1 gene silencing. Moreover, the co-delivery of DOX and SATB1 shRNA exhibited enhanced activity to inhibit gastric cancer cell growth in vitro and in vivo, compared to single delivery. In conclusion, the novel thermosensitive magnetic drug and gene co-delivery system has promising application in combined chemotherapy and gene therapy for gastric cancer.